2016
DOI: 10.2147/dddt.s110742
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of novel biodegradable ropivacaine microspheres and evaluation of their efficacy in sciatic nerve block in mice

Abstract: In this study, ropivacaine chitosan-loaded microspheres for subcutaneous administration were developed. The systems were characterized in terms of surface morphology, particle size, encapsulation efficiency, and in vitro release behavior. Results showed that the microspheres had drug loading rate of 7.3% and encapsulation efficiency of 91.2%, and their average diameter was 2.62±0.76 µm. The morphology study revealed that the microspheres are uniform monodispersed spheres and did not form aggregates in aqueous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In this study, the LA microparticle formulations were prepared by using SAP nanosheets to encapsulate RB particles in a soft-coating manner, which have shown two major advantages. On one hand, by forming a thin layer of peptide nanosheet coating around RB nano/micro-particles, this system achieved much higher capacity to encapsulate ropivacaine compared with previous strategies using traditional materials [40][41][42], which might greatly cut down the cost of fabrication. On the other hand, compared with our previously reported bottom-up strategies which were somehow complicated by relying on special interaction between LAs and the carrier materials, the current top-down strategy was much more straightforward and facile in obtaining particles with different size.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the LA microparticle formulations were prepared by using SAP nanosheets to encapsulate RB particles in a soft-coating manner, which have shown two major advantages. On one hand, by forming a thin layer of peptide nanosheet coating around RB nano/micro-particles, this system achieved much higher capacity to encapsulate ropivacaine compared with previous strategies using traditional materials [40][41][42], which might greatly cut down the cost of fabrication. On the other hand, compared with our previously reported bottom-up strategies which were somehow complicated by relying on special interaction between LAs and the carrier materials, the current top-down strategy was much more straightforward and facile in obtaining particles with different size.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the microsphere-formulated ropivacaine have shown promise in the controlled release of drugs. Chitosan microspheres loaded with ropivacaine hydrochloride show linear release [14]. Ropivacaine hydrochloride carried by poly(lactic-coglycolic acid) (PLGA) has been found to prolong the release period during animal experiments [15].…”
Section: Introductionmentioning
confidence: 99%